The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.46827/ejmms.v8i1.1392
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Impact Green Product Purchase Behaviour of Malaysian Shoppers

Abstract: Today, the rapid development of technology has caused both positive and negative effects and environmental changes. While enjoying the convenience provided by technology, people should have the right mindset in keeping and protecting their environment healthy. Therefore, this study aims to examine the factors that impact the green product purchase behaviour of Malaysian shoppers in Klang Valley, Malaysia. Five independent variables were used in this research project to identify the factors that influence worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Regarding the relationship between variables of the service marketing mix (7Ps) on sales performance, the research found a significant and insignificant relationship between the variables. For instance, (Saravanan et al, 2023;Li & Lee, 2019) conducted research that green marketing strategies have a positive impact on sales growth process variables and suggested that implementing such techniques of green products, green promotion, and the green process will aid in achieving desired sales growth levels. (Gituma, 2017), in his research, has established product quality, pricing strategy, and distribution channels located in urban has a positive impact on sales performance and recommended that the Unga Group should improve on their packaging design hence increasing product visibility and recognition.…”
Section: Research Problem Statementsmentioning
confidence: 99%
“…Regarding the relationship between variables of the service marketing mix (7Ps) on sales performance, the research found a significant and insignificant relationship between the variables. For instance, (Saravanan et al, 2023;Li & Lee, 2019) conducted research that green marketing strategies have a positive impact on sales growth process variables and suggested that implementing such techniques of green products, green promotion, and the green process will aid in achieving desired sales growth levels. (Gituma, 2017), in his research, has established product quality, pricing strategy, and distribution channels located in urban has a positive impact on sales performance and recommended that the Unga Group should improve on their packaging design hence increasing product visibility and recognition.…”
Section: Research Problem Statementsmentioning
confidence: 99%
“…Online shopping trends are influenced by many multidisciplinary and multidimensional factors that affect consumer behaviour (Saravanan et al, 2023;Kanapathipillai & Mahbob, 2021;Zhang, 2002). Subjective factors, like online consumer attitude and individual demands, and online buyers' objective factors, like web trust, product price, and quality, have contributed significantly to online buying behaviour.…”
Section: Online Purchasing Behaviourmentioning
confidence: 99%
“…Perception of the benefits associated with a specific shopping behaviour that was deemed to provide satisfaction to the individual. The functional or utilitarian perceptions of shopping on the internet are based on how effective the internet as a shopping medium is at assisting consumers in accomplishing the tasks they need to accomplish and how easy it is to navigate the internet as a shopping device (Saravanan et al, 2023;Overby & Lee, 2006;Nili, Delavari, Tavassoli & Barati, 2013). Regarding the reasons for the widespread perception of benefits, the most popular ones are related to ease of use, accessibility, and the convenience of time and energy.…”
Section: Relationship Between Perceived Benefits and Online Purchasin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Companies can use e-commerce to transact their business globally twenty-four hours a day without being limited by time and place. Companies can also use ecommerce to conduct business activities such as operational skills, provide various information to consumers, and connect with customers, to ensure they provide customers with perfect pre-sales and after-sales service (Sivaraman et al, 2023;Saravanan et al, 2023). With fierce competition in the market, many companies are actively maximizing their e-business services to provide better service to existing customers and attract new customers (Kajandren et al, 2023;Kanapathipillai & Kumaran, 2022).…”
Section: Introductionmentioning
confidence: 99%